Larynx and cervical trachea in humidification and heating of inhaled gases - Dias, Norimar Hernandes [UNESP]; Braz, José Reinaldo Cerqueira; Martins, Regina Helena Garcia; Carvalho, Lídia Raquel (SAGE Publications, 2005)
To evaluate the participation of the larynx and cervical trachea in conditioning inspired gases, we randomly allocated 16 mixed-breed dogs to two groups: group TT (tracheal tube; n = 8) and group LMA (laryngeal mask airway; n = 8). The dogs were anesthetized with pentobarbital sodium and mechanically ventilated for 3 hours. The parameters studied were temperature and absolute humidities of ambient, inhaled, and tracheal air. There was a small increase in tracheal air temperature compared to inhaled air temperature, but no significant difference between groups. The absolute humidity of tracheal air was greater in group LMA than in group TT (23 mg H2O·L-1 and 14 mg H2O·L-1, respectively; p < .0001). The difference in absolute humidity between the tracheal air and the inhaled air was higher in group LMA at all times (p < .0001). We conclude that the larynx and cervical trachea of the dog participate in humidification and heating of inhaled air by means of air contact with mucosa in this airway segment.
Keywords: Cervical trachea; Conditioning of air; Dog; Larynx